BeyondLife: An Open-Source Digital Will Solution for Posthumous Data Management - Xinzhang Chen; Arash Shaghaghi; Jesse Laeuchli; Salil S. Kanhere (IEEE Access)
Managing posthumous data is becoming an increasingly complex challenge, with many existing technical solutions proving impractical in real-world applications. Existing tools are typically closed-source, lack transparency, fail to offer cross-platform support, and provide limited access control. This paper introduces “BeyondLife”, a cross-platform, open-source, and privacy-enhancing digital will management solution designed to securely handle and distribute digital assets after death. At the core of this solution is a customized Ciphertext-Policy Attribute-Based Encryption (CP-ABE) scheme, referred to as PD-CP-ABE, which enables efficient, fine-grained control over access to will content at scale. Unlike existing systems, BeyondLife operates independently of service providers, offering users greater transparency and control over how their will is generated, stored, and executed. The system is designed to be portable, allowing users to change their will service provider. BeyondLife has been fully developed and evaluated to ensure performance and real-world feasibility. The security of PD-CP-ABE has also been formally proved using Tamarin Prover.